2019
DOI: 10.1093/infdis/jiz621
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Etiologies of Intussusception Among Children <2 Years Old in 4 Asian Countries

Abstract: Background The etiology of intussusception, the leading cause of bowel obstruction in infants, is unknown in most cases. Adenovirus has been associated with intussusception and slightly increased risk of intussusception with rotavirus vaccination has been found. We conducted a case-control study among children <2 years old in Bangladesh, Nepal, Pakistan, and Vietnam to evaluate infectious etiologies of intussusception before rotavirus vaccine introduction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 28 publications
(71 reference statements)
1
16
0
Order By: Relevance
“…A previous study reported fever in 40% of the intussusception cases ( 31 ). Viruses commonly cause intussusception in young children ( 4 ). A strong association between intussusception and the recent adenovirus infection has been reported in various populations, which may lead to the presentation of viral illness, including symptoms of fever or diarrhea, before the onset of intussusception ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study reported fever in 40% of the intussusception cases ( 31 ). Viruses commonly cause intussusception in young children ( 4 ). A strong association between intussusception and the recent adenovirus infection has been reported in various populations, which may lead to the presentation of viral illness, including symptoms of fever or diarrhea, before the onset of intussusception ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intussusception is a common abdominal emergency in children ( 1 3 ). Its misdiagnosis and delayed diagnosis in children is common because its symptoms at presentation are highly atypical, mimicking other conditions such as acute gastroenteritis and viral infections ( 4 , 5 ). The misdiagnosis and delayed treatment of intussusception may lead to severe morbidities including intestinal ischemia, necrosis, perforation, or even mortality ( 6 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…These viral infections were characterized by cough, nasal discharge, and diarrhea. Other studies also found an association between viral infections and intussusception [19,20].…”
Section: Discussionmentioning
confidence: 87%
“…However, there is a very strong casual association between viruses, mesenteric lymphoid hyperplasia and intussusception ( 9 ). In particular, adenovirus, enterovirus, norovirus, rotavirus and human herpes virus 6 have been associated with intussusception in infants and young children ( 10 ). To the best of our knowledge, eight cases of intussusception being the presentation of COVID-19 in infants have been reported so far ( 11 17 ).…”
Section: Discussionmentioning
confidence: 99%